2014
DOI: 10.1038/srep03735
|View full text |Cite
|
Sign up to set email alerts
|

Selenite reduction by Shewanella oneidensis MR-1 is mediated by fumarate reductase in periplasm

Abstract: In situ reduction of selenite to elemental selenium (Se(0)), by microorganisms in sediments and soils is an important process and greatly affects the environmental distribution and the biological effects of selenium. However, the mechanism behind such a biological process remains unrevealed yet. Here we use Shewanella oneidensis MR-1, a widely-distributed dissimilatory metal-reducing bacterium with a powerful and diverse respiration capability, to evaluate the involvement of anaerobic respiration system in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(145 citation statements)
references
References 57 publications
3
137
0
Order By: Relevance
“…A recent study on selenite reduction by Shewanella oneidensis MR-1 indicated that a deletion of cymA results in an inability to reduce selenite. Deleting the flavocytochrome c-encoding gene fccA led to lower selenite reduction rates, which seems to be in agreement with a role for flavocytochrome c as an electron shuttle, although it cannot be ruled out that FccA acts as the terminal selenite reductase (67). Methacrylate reduction in Geobacter sulfurreducens AM-1 was shown to be carried out by a periplasmic flavoprotein tetraheme cytochrome c complex (47).…”
Section: Discussionsupporting
confidence: 48%
“…A recent study on selenite reduction by Shewanella oneidensis MR-1 indicated that a deletion of cymA results in an inability to reduce selenite. Deleting the flavocytochrome c-encoding gene fccA led to lower selenite reduction rates, which seems to be in agreement with a role for flavocytochrome c as an electron shuttle, although it cannot be ruled out that FccA acts as the terminal selenite reductase (67). Methacrylate reduction in Geobacter sulfurreducens AM-1 was shown to be carried out by a periplasmic flavoprotein tetraheme cytochrome c complex (47).…”
Section: Discussionsupporting
confidence: 48%
“…Interestingly, little reduction was observed using lactate as the electron donor, and no reduction at all was achieved using acetate or formate as the electron donor (53 reduction. Until now, detailed investigation of SeO 3 2Ϫ reduction via respiratory electron transport pathways was limited to a single study using S. oneidensis MR-1 (55). More details on the roles of respiratory reductases and the electron transport pathway in S. oneidensis MR-1 for SeO 3 2Ϫ reduction are described below.…”
Section: Selenite-respiring Bacteriamentioning
confidence: 99%
“…9). Mutant strains defective in periplasmic terminal reductases, i.e., nitrate reductase (NapA), nitrite reductase (NrfA), and fumarate reductase (FccA), and periplasmic mediators of anaerobic respiration, i.e., MtrA and DmsE, were tested for SeO 3 2Ϫ reduction ability (55). The ⌬napA and ⌬nrfA mutant strains reduced selenite at the same rate as wild-type S. oneidensis MR-1.…”
Section: Selenite Reductionmentioning
confidence: 99%
“…The reduction of selenite is reported to take place through dissimilatory respiration and the BioSeNPs are mainly formed in the periplasm or extracellularly [24,25]. Prior to batch adsorption experiments, BioSeNPs were characterized by X-ray diffraction (XRD), Scanning Electron Microscopy -Energy Dispersive X-ray Spectroscopy analysis (SEM-EDXS), ζ-potential measurements and X-ray photoelectron spectroscopy (XPS).…”
Section: Introductionmentioning
confidence: 99%